2004
DOI: 10.1021/jp0482565
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Ion and Water Transport in Perfluorosulfonated Ionomer Membranes for Fuel Cells

Abstract: To clarify transport mechanisms of ions and water molecules in perfluorosulfonated ionomer membranes, various membranes, such as one Nafion, two Aciplex, and four Flemion types, having different equivalent weight values (EW) were examined. H-, Li-, and Na-form samples were prepared for each membrane by immersion in 0.03 M HCl, LiCl, and NaCl aqueous solutions, and their properties in the fully hydrated state were investigated systematically. The water content of the membranes showed the tendency that the size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
181
1
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(203 citation statements)
references
References 32 publications
16
181
1
4
Order By: Relevance
“…Once the cations enter the ionomer, they displace protons resulting in reduced ionic conductivity and water content, as well as lower gas permeability of the ionomer. 5,6,[13][14][15][16][17][18] Other researchers confirmed the findings of Okada group as well. 9,20,25,31,33 23 Pozio et al 19 investigated the degradation in PEFC that was caused by iron contamination from SS316L end plates and reported that contamination of the membrane electrode assemblies with iron led to degradation of the ionomer, revealed by a massive fluoride losses.…”
supporting
confidence: 61%
“…Once the cations enter the ionomer, they displace protons resulting in reduced ionic conductivity and water content, as well as lower gas permeability of the ionomer. 5,6,[13][14][15][16][17][18] Other researchers confirmed the findings of Okada group as well. 9,20,25,31,33 23 Pozio et al 19 investigated the degradation in PEFC that was caused by iron contamination from SS316L end plates and reported that contamination of the membrane electrode assemblies with iron led to degradation of the ionomer, revealed by a massive fluoride losses.…”
supporting
confidence: 61%
“…Figure 6.18a shows the FTIR spectra of S (25) As shown in Table 6 The mobile cations move through the water-swollen polymer and water facilitates cation transport from sulfonate group to sulfonate group. 65,148 Therefore, the mobility of the ions depends on the swelling degree of the matrix. 65 The water swelling of S(25)PAEK and S (25) …”
Section: Resultsmentioning
confidence: 99%
“…65,148 Therefore, the mobility of the ions depends on the swelling degree of the matrix. 65 The water swelling of S(25)PAEK and S (25) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As diferentes membranas diferem basicamente quanto à composição, densidade e comprimento dos grupos laterais de forma que ambos alteram o estado de agregação dos íons na matriz que influenciam nas propriedades elétricas do ionômero. Estudos sobre a morfologia e as propriedades de transporte de água e íons destes materiais apontaram as membranas Nafion e Dow como os eletrólitos mais apropriados para aplicações em células a combustível de baixa temperatura [21,22,23].…”
Section: Ionômero áCido Perfluorosulfonado Nafionunclassified